The Prevalence of Hepatitis A Virus and Hepatitis E Virus in a tertiary care hospital, East Delhi, India.: Charu Jain , Nikita Birhman , Shukla Das , Swati Sinha, N.P. Singh - Jain, Charu; Birahman, Nikita; Das, Sukhla; Sinha, Swati; Singh, N.P (UNUSA Press, 2023)
Background & Aim: Acute viral hepatitis (AVH) is a condition that is known to be caused by enterically transmitting Hepatitis A virus (HAV) and Hepatitis E virus (HEV). Usually, they result in self-limiting disease but can be seriously threatening if complications arise. This study was done to determine the prevalence rate of HAV and HEV in a tertiary care hospital in East Delhi, India. Material & Methods: The retrospective and observational study of 2-year duration was conducted in the Department of Microbiology at UCMS and GTBH Delhi, India. A total of 410 samples from patients presenting with a clinical diagnosis of acute hepatitis were considered in the study. The serum samples were analysed for IgM anti-HAV and IgM anti-HEV, respectively, using commercially available ELISA kits. Results: The seroprevalence of HAV and HEV were 2.19% and 0.24%, respectively. No case was found to be reactive for both parameters, indicating no case of co-infection. The majority of clinical samples were from female patients. Conclusion: The incidence of HEV and HAV illnesses suggests that East Delhi has a lower prevalence rate of the reported viral illnesses. This finding suggests one of the following: limited circulation of the agents, good sanitary conditions, and/or protective immunity among the population tested. Nonetheless, we should continue to assess the ongoing conditions and take measures to improve them.